Unable to resist temptation: How self-control depletion promotes unethical behavior - Gino, Francesca; Schweitzer, Maurice E.; Mead, Nicole L.; Ariely, Dan (Organizational behavior and human decision processes, 2011)
Across four experimental studies, individuals who were depleted of their self-regulatory resources by an initial act of self-control were more likely to “impulsively cheat” than individuals whose self-regulatory resources were intact. Our results demonstrate that individuals depleted of self-control resources were more likely to behave dishonestly (Study 1). Depletion reduced people’s moral awareness when they faced the opportunity to cheat, which, in turn, was responsible for heightened cheating (Study 2). Individuals high in moral identity, however, did not show elevated levels of cheating when they were depleted (Study 3), supporting our hypothesis that self-control depletion increases cheating when it robs people of the executive resources necessary to identify an act as immoral or unethical. Our results also show that resisting unethical behavior both requires and depletes self-control resources (Study 4). Taken together, our findings help to explain how otherwise ethical individuals predictably engage in unethical behavior.